Oatmeal and wheat flour as the sources of thyroid peroxidase and proinflammatory enzymes modulators in the prevention of thyroid diseases - Urszula Gawlik; Ewa Habza-Kowalska; Katarzyna Piwowarczyk; Jarosław Czyż; Urszula Złotek (Scientific Reports)
Abstract Polyphenolic plant compounds possess nutritional and pro-healthy potential, reducing the risk of auto-inflammatory and neoplastic diseases. However, their interference with the progression of thyroid gland dysfunctions has remained largely unaddressed. For this purpose, we combined the analyses of phenolic content and antioxidative activity with the thyroid peroxidase (TPO), lipoxygenase (LOX), xanthine oxidase (XO) and cyclooxygenase-2 (COX-2) activity assays, isobolographic approach and the estimation of thyroid cancer cells’ proliferation and motility in vitro. Bioaccessible oatmeal (OM) and wheat flour (WF) compounds activated TPO while inhibiting LOX and XO’s in vitro activity. OM extracts also inhibited COX-2 activity. Isobolographic and combination index studies revealed cooperation of compounds from OM and WF. However, the relatively strong inhibitory activity of bioaccessible OM compounds on LOX activity correlated with their mildly cytostatic and relatively distinct pro-invasive effects in the thyroid cancer model in vitro. Collectively, the application of OM and WF products for the prophylactics of inflammatory thyroid diseases should be considered with care, especially in the context of the oncological status of the patient.